The New Chilean Migration Law:Analysis of Its Configuration as a Discursive Power Dispositif - Brower-Beltramin, J (UNAM, FAC CIENCIAS POLITICAS & SOCIALES, 2024)
In this note, we present some of the preliminary results of our research, limited to the new Chilean migration law (N degrees 21,325), in its discursive dimension. The analysis carried out has as a theoretical/con-ceptual referent the term dispositif as knowledge/power, developed by Michel Foucault. We approached the discursive expression of this legal corpus through specific articles. Based on this theoretical design, we elaborate an ad hoc methodology to analytically review the corpus in question, identifying the semantic and ideological model that this law contains regarding migration, the subjects involved, and the type of regulation established in a larger context, which obey certain historical and political coordinates.